40-GHz transimpedance amplifier with differential outputs using InP-InGaAs heterojunction bipolar transistors. - Wu, C.Q (IEEE Journal of solid state circuits)
High-gain and high-bandwidth transimpedance amplifiers (TIAs) are required for fiber-optic receiver modules. This paper reports on the design, fabrication, and characterization of a 40-Gb/s TIA for SONET/SDH STS-768/STM-256 applications based on an InP-InGaAs single heterojunction bipolar transistor (SHBT) process developed at Vitesse Semiconductor Corporation (Vitesse Indium Phosphide Release 1 or VIP-1). This amplifier consists of a single-ended input transimpedance pre-amplifier and a differential output post-amplifier. The measured differential transimpedance is 1800 Ω with -3-dB bandwidth greater than 40 GHz. The high gain of this circuit eliminates the need for a standalone limiting amplifier between the conventional transimpedance pre-amplifier and the demultiplexer in short-reach applications.